2004
DOI: 10.3189/172756404781814474
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere–snow interaction by a comparison between aerosol and uppermost snow-layers composition at Dome C, East Antarctica

Abstract: The study of aerosol composition and air–snow exchange processes is relevant to the reconstruction of past atmosphere composition from ice cores. For this purpose, aerosol samples, superficial snow layers and firn samples from snow pits were collected at Dome Concordia station, East Antarctica, during the 2000/01 summer field season. The aerosol was collected in a ‘coarse’ and a ‘fine’ fraction, roughly separated from each other by a stacked filter system (5.0 and 0.4 μm). Atomic Force Microscopy (AFM) direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 30 publications
9
75
0
Order By: Relevance
“…At a given temperature, k eff H increases by an order of magnitude between pH 5 and 6.5 (Fig. B3a), the typical range of pH in natural snow (Udisti et al, 2004). While at a given pH, k eff H decreases by 2 orders of magnitude between −40 and 0 • C (Fig.…”
Section: Coexistence Of Liquid Solution With Icementioning
confidence: 99%
See 1 more Smart Citation
“…At a given temperature, k eff H increases by an order of magnitude between pH 5 and 6.5 (Fig. B3a), the typical range of pH in natural snow (Udisti et al, 2004). While at a given pH, k eff H decreases by 2 orders of magnitude between −40 and 0 • C (Fig.…”
Section: Coexistence Of Liquid Solution With Icementioning
confidence: 99%
“…B3b). Note that the range of pH measured by Udisti et al (2004) is the pH of the melted sample, which might be different from the pH of the liquid fraction of the snow grain not observable by current measurement techniques.…”
Section: Coexistence Of Liquid Solution With Icementioning
confidence: 99%
“…Udisti et al [7] collected atmospheric aerosol, superficial snow layers and firn samples from snow pits at Dome Concordia station during the 2000/2001 summer field season. Comparative analysis of aerosol, surface hoar and surface snow showed differences in chemical composition.…”
Section: Nomentioning
confidence: 99%
“…concentrations in snow and in air are sometimes related and sometimes not [7] [9] [16] [17] [19] [20]. Published papers frequently compared ion concentration (soluble and/or insoluble) in snow and aerosol, neglecting to discuss the fact that snow could also scavenge chemical compounds in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…At Dome C on the Antarctic plateau, it was demonstrated that nitrate and chloride can be caught by the surface snow through dry deposition and adsorption processes (Udisti et al, 2004). The interactions of carboxylic acid at the air-snow interface has been studied in the Arctic (Narukawa et al, 2002), and underlined the compositional difference between aerosol and snow samples.…”
Section: Introductionmentioning
confidence: 99%